COMPUTER SYSTEM AND MODELLING OF THREATS TO ENERGY SECURITY OF MOLDOVA IN CASE OF INTERSYSTEM COMMUNICATION DISCONNECTION - Bicova E.V. (Problems of the Regional Energetics, 2010)
In the paper modeling of a group of scenarios of threats to energetic security of Moldovan energy system, which occur in case of disconnecting (or limitation of cross-flows of electricity) of 330 kV transmission line Balti-Dniester HPS. It was used for analysis a software application for energy security monitoring. The application has been developed in IE ASM.